The Influence of Tourism Attribute on Tourist's Perceived Value of the Tourism Community-Based in The Khong River Basin, Nong Kai Province - Phonphithak, Kannika; Pimpuang, Teerawat; Laon, Teerawut; Wongchomphu, Warisara; Chaisuk, Sirisak; Meeprom, Supawat (KKBS Journal of Business Administration and Accountancy, 2020)
The objective of this study is to investigate the influence of tourism attributes on tourist’s perceived value of the tourism community-based in The Khong River Basin, Nong Khai Province. This study used a self-administrative approach to collected the data from tourists who visited the five destinations of Community-Based Tourism in Nong Khai province. 150 useable data were used to formulate the hypothesis testing. The multiple regression analysis was utilized to test the proposed hypotheses. The research found that (1) Availability, (2) Activities, (3) Amenities have positively and significantly influence on perceived value of tourism destination. The findings of the study suggest that tourism operators in the community should pay more attention to tourism components in order to increase the level of tourist’s satisfactions and values.